Appeal From The High Court To The Court Of Appeal Against A Bail Decision: Dato’ Seri Anwar Ibrahim V Public Prosecutor - Majid, Mimi Kamariah (Journal of Malaysian and Comparative Law, 1999)
In the case of Dato’ Seri Anwar Ibrahim V Public Prosecutor three major points were discussed. The first was in relation to the question of whether a bail decision by the High Court is appealable to the Court of Appeal.